Peningkatan Keterampilan Berbicara Menggunakan Media Gambar Pada Siswa Sekolah Dasar - Desra, Eriza (Faculty Of Education, 2024)
This research was motivated by the low speaking skills of students in thematic learning in class V UPT SD Negeri 009 Kebun Tinggi. One solution to overcome this problem is to use image media. This research aims to determine the improvement of students' speaking skills using image media in class V students at UPT SD Negeri 009 Kebun Tinggi. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementing, observing, reflecting, and when the research was carried out in January 2024. The research subjects were 5 class V students, with 2 males and 2 female students. totaling 3 students. Data collection techniques include documentation, observation and tests. The results of this research can be concluded that image media can improve students' speaking skills in class V UPT SD Negeri 009 Kebun Tinggi s. In cycle I, the results of students' speaking skills were classified as poor with a percentage of 40%. Next in cycle II with a percentage of 100% in the very good category. Of 5 students. Thus, it can be concluded that using image media can improve the speaking skills of class V students at UPT SD Negeri 009 Kebun Tinggi for the 2023/2024 academic year.